Design, Synthesis and Biological Evaluation of 1-methyl-1H-pyrazole-5-Carboxamide Derivatives as Novel Anti-Prostate Cancer Agents - Chen, Xin; Xu, Changqing; Li, Yuxia; Duan, Xiaoming; Zhao, Guisen (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: The Androgen Receptor (AR) signaling functionis a critical driving force for the progression of Prostate Cancer (PCa) to bring about anti-prostate cancer agents, and AR has been proved to be an effective therapeutic target even for Castration-Resistant Prostate Cancer (CRPC). Objective: In order to discover novel anti-prostate cancer agents, we performed structural modifications based on the lead compounds T3 and 10e. Methods: A set of 1-methyl- 1H-pyrazole-5-carboxamide derivatives were synthesized and evaluated for their inhibitory activities against both expressions of Prostate-Specific Antigen (PSA) and growth of PCa cell lines. Results: Compound H24 was found to be able to completely block PSA expression at 10μM, and showed prominent antiproliferative activity in both the LNCaP cell line (GI50 = 7.73μM) and PC-3 cell line (GI50 = 7.07μM). Conclusion: These preliminary data supported a further evaluation of compound H24 as a potential agent to treat prostate cancer.
Keywords: Androgen receptor